Perceptual, Not Attentional, Guidance Drives Happy Superiority in Complex Visual Search - Sjoerd M. Stuit; M. Alejandra Pardo Sanchez; David Terburg (Behavioral Sciences)
Emotional facial expressions are thought to attract attention differentially based on their emotional content. While anger is thought to attract the most attention during visual search, happy superiority effects are reported as well. As multiple studies point out confounds associated with such emotional superiority, further investigation into the underlying mechanisms is required. Here, we tested visual search behaviors when searching for angry faces, happy faces, or either happy or angry faces simultaneously using diverse distractors displaying many other expressions. We teased apart visual search behaviors into attentional and perceptual components using eye-tracking data and subsequently predicted these behaviors using low-level visual features of the distractors. The results show an overall happy superiority effect that can be traced back to the time required to identify distractors and targets. Search behavior is guided by task-based, emotion-specific search templates that are reliably predictable based on the spatial frequency content. Thus, when searching, we employ specific templates that drive attentional as well as perceptual elements of visual search. Only the perceptual elements contribute to happy superiority. In conclusion, we show that template-guided search underlies perceptual, but not attentional, happy superiority in visual search.